Functional Properties of Casein Added with Catechin Extracted from Cocoa Husk - Premy Puspitawati Rahayu; Djalal Rosyidi; Purwadi Purwadi; Imam Thohari (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2019)
Casein is one of the major protein components in milk. Its functional properties allow casein to be preferred by the consumers. In addition, casein could be collected as bioactive compositions to be added to food. The purpose of this study was to observe the functional properties of casein added with catechin from cocoa husk in terms of emulsions, emulsion activity, foaming, solubility, and sedimentation. The treatment was carried out by using a completely randomized experimental design (CRD) method with five treatments of different catechin concentrations (control; 0.5%; 1,0%; 1,5%; 2%). The results of the study were analyzed with analysis of variance and followed with least significant difference (LSD) test. The different catechin concentrations gave a highly significant effect on emulsion stability, foaming and sedimentation and didn’t give a significant difference in solubility and emulsion activity between the five treatments. The best treatment in this research was at 2% catechin addition.